2020
DOI: 10.5334/aogh.2671
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of HIV and Hepatitis C among Internally Displaced Persons in Georgia

Abstract: Background: Georgia is leading one of the world's first hepatitis C (HCV) elimination programs alongside interventions to combat a HIV epidemic concentrated among high-risk groups. Although progress has been substantial, neither strategy accounts for the nearly 150,000 internally displaced persons residing in collective centers (CC-IDPs) who are susceptible to deeply integrated risk environments that could promote infection. Achieving dedicated goals for HCV elimination and HIV suppression requires a clear und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Poor living conditions may also facilitate transmission in some IDP populations. In Georgia, one study suggested a geographic concentration of HIV and hepatitis infection in areas with greater clusters of IDPs residing in collective centres with poor living conditions ( Elbaz, 2020 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…Poor living conditions may also facilitate transmission in some IDP populations. In Georgia, one study suggested a geographic concentration of HIV and hepatitis infection in areas with greater clusters of IDPs residing in collective centres with poor living conditions ( Elbaz, 2020 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…Ensure the identification of people with HIV, considering Ukrainian key populations with a high HIV prevalence [38][39][40][41][42] Registration of patients (including refugees) in need of ART; a proactive approach by health-care providers to identify those with HIV in key populations and overcome stigma; sufficient operational HIV expert teams on the ground; medical outreach teams to reach remote areas or areas without operational clinics because of warfare…”
Section: Key Population Supportmentioning
confidence: 99%
“…Studies have shown that the HIV prevalence in people displaced from HIV endemic settings is high. [38][39][40][41] With the focus of the war now in the eastern, southern, and central parts of Ukraine, the population of people with some of the highest HIV infection rates in the country is affected and deprived of access to harm-reduction programmes, resulting in a high chance of viral spread because of migration internally and internationally. 10,62 Convincing evidence exists that adequate HIV treatment and linkage to care programmes are effective during war, and HIV networks should support implementing these initiatives, regardless of the local situation.…”
Section: Hiv Care Transfer and Continuationmentioning
confidence: 99%
“…Research on displaced people in Malaysia and Kenya showed that intervention to increase individual's resilience and reduce food and health insecurities might help improve ART adherence [74]. Furthermore, both people with a history of displacement and PLWH are more likely to have symptoms of depression and anxiety [52,53], which can be another barrier to treatment adherence [40,75].…”
Section: Antiretroviral Therapy (Art) Initiation and Adherencementioning
confidence: 99%
“…Poor psychosocial health and mental wellbeing arising from the traumatic events many displaced people have experienced [52,53] and exacerbated by discrimination, barriers to social and economic inclusion, and difficulties accessing healthcare services [5,13] may be associated with HIV risk behaviours, particularly sexual risky behaviours, such as less frequent condom use, among forced migrants [18,54]. Alcohol and drug use can be a form of coping with traumatic experiences and other stressors in contexts of displacement [55], which can in turn increase the probability of engaging in behaviours that increase HIV risk [53].…”
Section: Individual and Behavioural Factorsmentioning
confidence: 99%